Transitioning from an economic cluster to a collaborative community: Mining projects in Greenland - Maja Due Kadenic (Journal of Organization Design, 2017)
This paper analyzes the Greenlandic business community and the recently established cluster relevant to extractive industries in Greenland, Arctic Cluster of Raw Materials (ACRM), to enhance local business development in mining projects in Greenland. The analysis directs toward a transition from an economic cluster to a collaborative community in order to increase business potential and to overcome limitations of smallness and inadequate competencies of the Greenlandic business community in the mining industry. Transitioning into a collaborative community creates more value by enabling member firms to realize business development that each single firm could not achieve with its own efforts by being a part of a cluster. Managing the transition process emphasizes the facilitating role for the reason that a shared service provider is required in every collaborative community. I develop a conceptual model for the transition from an economic cluster to a collaborative community based on the architectural elements of the collaborative community design. The conceptual model considers the five proximity dimensions that influence inter-firm linkages both as enablers and barriers to the transition process and collaboration. Collaboration represents a new approach to business and industrial development in remote regions of the Arctic, as challenges evident for Greenland can be found throughout the entire Arctic.
Keywords: 650; Cluster development; Collaboration; Collaborative community; Proximity dimensions; Greenland; Mining; Arctic